مفاهيم الحداثيين العرب حول ظاهرة الوحي في حديث الغار :bدراسة قرآنية تحليلية /cإعداد، محمد حافظ بن أبي بكر - Mohd Hafiz Abu Bakar (Kulliyat Ma'arif al-Wahy wa al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah Maliziya, 2010)
The research aims to study the new trends undertaken by some Arab modernists towards the revelation of the Qur'an as conceived from the event of the cave of Hira'. It uncovers the deficiencies of the trend, recognizes its challenges and rebuts its propositions launched to disparage the authenticity of the holy Qur'an . This study critically deals with the thoughts of these modernists such as Nasr Hamid Abu Zaid, Hisham Ju'ait, Mohammad Shahrour, Mohammad Arkoun and Sodiq Nayhum and examines it based on the clear Islamic text and sound human reasoning. Hence, the study deals with the concept of wahy from Islamic perspective and deliberates on the report of the Cave of Hira', which demonstrated the beginning of the revelation of the Qur'an on the Prophet (peace be upon him). The study explains the status of this hadith on the basis of sanad (i.e. chain of narrators) and matn (i.e. text of hadith) and deals with assumptions held by the Arab modernists to reject this hadith. It relates the appropriate meaning of the word 'Qira'ah' or 'read' in detail. Besides, the study also demonstrates the issue of 'word formation of the Qur'an ' from modernists' approach and provides an objective critical analysis. The study relies on the analytic and inductive methodologies to arrive at conclusions. It uses the inductive method to review all related literatures to the subject, while it examines the thoughts of these modernists as portrayed in their texts based on the analytic method. Subsequently, the research reaches some significant conclusions. It considers this new trend a product inherent in the Western scheme to raise doubts about the noble Qur'an and its revelation. Also, the major approaches employed to saturate this notion depend largely on assumptions, rare weak opinions which did not pass the test of sound scientific methodology and did not conform to the bases of the Arabic language and literature. This study proves that the modernists approach aimed at devaluing the Qur'an and its status to eradicate Islamic culture and religion.